Self-Acceptance and Psychological Burden In Autism: A Narrative Review - Andien Putri Eltrid; Raini Diah Susanti; Nenden Nur Asriyani Maryam (Universitas Malahayati Lampung, 2026)
ABSTRACT Fathers of children with autism spectrum disorder (ASD) often commonly experience psychological burdens that are less frequently explored compared to mothers. This narrative review aims to synthesize existing evidence regarding the psychological burden, self-acceptance, and psychological adaptation of fathers who have children with autism. This study used a narrative review design. Articles published between 2019 and 2025 were systematically retrieved from databases including PubMed, Scopus, ScienceDirect, Google Scholar, and Garuda. To make sure the chosen studies were timely and relevant, a manual screening process based on predetermined inclusion criteria was carried out. A total of 11 studies were reviewed and synthesized narratively. The findings indicate that fathers of children with autism experience various psychological burdens, including stress, anxiety, depressive symptoms, stigma, identity conflict, and social withdrawal. However, self-acceptance are associated with better psychological well-being, parenting quality, and family functioning. The development of self-acceptance is essential to enhancing the psychological well-being and caregiving ability of fathers of autistic children, despite the various psychological burdens they confront. Interventions focusing on psychological support and paternal involvement are essential to strengthen family resilience. Keywords: Autism, Fathers, Self-acceptance, Psychological Burden, Well-being.